Physicochemical, Organoleptic Properties, and Acceptability of Natural Seasoning Powder Made from Chicken Feet and Tomato - Siti Nurfuzti Fauziah; Desy Triastuti; Wiwik Endah Rahayu (EDUFORTECH, 2023)
The seasoning powder is a flavor enhancer to improve the taste of food. Chicken feet and tomatoes contain glutamic acid that potentially uses in seasoning making. This research was focused on the making of natural chicken feet seasoning powder with the addition of tomatoes. A food dehydrator was used in this study for maintaining constant airflow and constant temperature during the drying stage. Optimum conditions for the chicken feet seasoning powder were determined by varying the addition of tomatoes (0, 20, 30, and 40%). The physicochemical properties such as color, solubility, and moisture content, and organoleptic properties such as taste, aroma, texture, and acceptability were analyzed. Data were statistically analyzed using ANOVA (Analysis of Variance) and the significant difference between the samples was determined using DMRT at p5% respectively. The addition of tomatoes had a significant effect on the parameters of water content, taste, and panelist's level of preference, and had no significant effect on the parameters of solubility, aroma, and texture. The higher addition of tomatoes produces a flavor with a reddish-brown color (Irish coffee). The best treatment results were T3 (40%) which had an Iris coffee color, a solubility of 67.67 seconds, a water content of 3.84%, a savory taste, no fishy smell, and fairly smooth texture, and was preferred by panelists.